FEATURES AND DISADVANTAGES OF QUOTAS OF JOBS FOR PEOPLE WITH DISABILITIES IN UKRAINE (INNOVATIVE ECONOMY, 2020)
Overchuk V.A. FEATURES AND DISADVANTAGES OF QUOTAS OF JOBS FOR PEOPLE WITH DISABILITIES IN UKRAINEPurpose. The aim of the article is to find out the specifics and identify the disadvantages of quotation of persons with disabilities in Ukraine.Methodology of research. General scientific and special methods are used in the process of research, in particular: the method of comparative analysis is used to substantiate the feasibility of taking into account the conditions of functioning of enterprises in determining the value of the standard of workplaces; the methods of induction and deduction are used in identifying the need for periodic update of information at the departments of the Fund for Social Protection of the Disabled and the State Employment Service. The method of system analysis is used to establish the need for elaboration of the criteria for the submission of vacancies for persons with disabilities to the legal norms.Findings. The necessity of supplementing the normative documents with the obligation of employers to inform the Fund’s departments of the change in the number of employees, or the liquidation or reorganization of the enterprise, and periodically update information at the State Employment Service about available vacancies for persons with disabilities is determined. The necessity of developing criteria for the analysis of vacancies submitted to employment centres for persons with disabilities is substantiated.Originality. A methodical approach to the analysis of quota of workplaces is developed, which, unlike the current one, considers the activities of all subjects in the context of facilitating the employment of persons with disabilities and reveals conflicts of interests, the elimination of which helps to increase the efficiency of quotation of the work places of persons with disabilities.Practical value. The obtained results can be used in shaping the social policy of the state in promoting the employment of persons with disabilities, in particular, in the activities of the State Employment Service and the Fund for Social Protection of Persons with Disabilities. Taking into account proposals will increase the level of implementation of the norm by employers, and will promote better implementation of the labour potential of the state and certain categories of citizens.Key words: labour market; person with disabilities; employment; norm of employment of persons with disabilities; quotation of workplaces.
Keywords: Key words; labour market; person with disabilities; employment; norm of employment of persons with disabilities; quotation of workplaces.